Pure retroperitoneoscopic donor nephrectomy in duplication of inferior vena cava: A series of four cases - Pal, Bipin Chandra (Urol Ann, 2017)
AIM: Complex vascular anatomy poses a major challenge to the donor surgeon. Here, we have described the technical nuances in retroperitoneoscopic living donor nephrectomy for the left kidney in the situations of a rare vascular anomaly of duplication of inferior vena. MATERIALS AND METHODS: Between September 2005 and June 2016, 1460 retroperitoneoscopic living donor nephrectomy were carried out in single surgical unit of our institution. Out of these four donors were found to have duplication of inferior vena cava (IVC). We retrospectively analyzed the prospectively collected data of these donors and studied the operative details for managing the duplicated limb of the IVC. RESULTS: The mean age of the donors was 42.5 (range 30–54) years. Mean body mass index was 26.9 (range 25.2–28.6) kg/m(2). Mean operative time (defined as between giving skin incision to the skin closure [O. T]), was 230 (range 185–310 min). Mean Warm ischemia time (defined from clamping of the renal artery to the starting of the cold HTK perfusion, [WIT]) was 136 s (range 105–178 s). In two cases, the renal vein could be controlled distal to the duplicated limb. In one case, the duplicated limb was clipped while in another a stapler was used to take a cuff of IVC. CONCLUSION: Retroperitoneoscopic donor nephrectomy can be performed safely in cases of duplication of IVC. Preoperative computerized tomography angiography with vascular reconstruction and surgical expertise is desirable in carrying out the procedure.